Heterotrimeric G-protein effectors - Iyengar, Ravi (Methods in enzymology, 1994)
This volume of Methods in Enzymology and its companion Volume 237 include molecular, biological, and biochemical methods for the study of cell surface heterotrimeric G proteins and their effectors. Methods unique to signal transducing G proteins and general techniques that have been applied to the study of G protein systems are covered.